An Analysis of Code-Mixing in Bunga Citra Lestari’s Love Story #1 – BCL Sebelum & Sesudah Ashraf - Nazak, Ahlul; Fhitri, Widya; Antaridha, Rabbi; Maiza, Thiska Septa; Shabri, Irsyad (LPPM Universitas Dharma Andalas, 2023)
This research is aimed at finding out types and forms of code-mixing in the video from Bunga Citra Lestari’s YouTube channel entitled Love Story #1 – BCL Sebelum & Sesudah Ashraf. This research uses descriptive qualitative method. The data in this study is a video from the Bunga Citra Lestari’s YouTube channel entitled Love Story #1 – BCL Sebelum & Sesudah Ashraf. In collecting the data, this research used Heed Method. The method is then followed by an independent see-engage-talk technique. Data analysis used in the research is the agih method with an indirect element technique. After conducting the analysis, it was found that there are code-mixing 33 data in the video. There are 24 data for types of code-mixing and 37 data for forms of code-mixing. In the types of code-mixing, there are 15 insertion data, 6 substitution data, and 10 congruent lexicalization data, while for the forms of code-mixing, there are 18 data in the form of word, 3 data in the form phrase, 1 data in hybrid form, and 15 data in the form of clause.